1999
DOI: 10.1128/iai.67.8.3952-3959.1999
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Staphylococcus aureus Collagen Adhesin B Domain

Abstract: The Staphylococcus aureus collagen adhesin (CNA) occurs in at least four forms that differ in the number (one, two, three, or four) of B domains. The B domains contain 187 amino acids and are located between the domains that anchor CNA to the cell envelope and the ligand-binding A domain. To determine whether a B domain is required for functional expression of CNA, we cloned the 2Bcna gene from S. aureus strain Phillips and then eliminated both B domains by overlapping PCR. The absence of a B domain did not af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…It has been suggested that the S. mutans Cnm and Cbm use a similar mechanism to bind collagen (Kang et al ., ), although the crystal structure for either protein has yet to be resolved. The B domain of Cna, composed of one to four repeating subunits of 23 kDa, does not alter the capacity of the A domain to interact with collagen (Rich et al ., ; Snodgrass et al ., ). Although the Cna B‐domain does not appear to be glycosylated, the B domain of Cnm undergoes O ‐glycosylation, a process that was shown to confer proteolytic stability and, possibly, function (Avilés‐Reyes et al ., ).…”
Section: Current Knowledge and Potential Gapsmentioning
confidence: 97%
“…It has been suggested that the S. mutans Cnm and Cbm use a similar mechanism to bind collagen (Kang et al ., ), although the crystal structure for either protein has yet to be resolved. The B domain of Cna, composed of one to four repeating subunits of 23 kDa, does not alter the capacity of the A domain to interact with collagen (Rich et al ., ; Snodgrass et al ., ). Although the Cna B‐domain does not appear to be glycosylated, the B domain of Cnm undergoes O ‐glycosylation, a process that was shown to confer proteolytic stability and, possibly, function (Avilés‐Reyes et al ., ).…”
Section: Current Knowledge and Potential Gapsmentioning
confidence: 97%
“…Concerning the repetitive B-region in collagen-binding MSCRAMMs, so far, the crystal structure consisting of two (PDB ID 1D2O) and four B-repeats (PDB ID 1D2P) (we considered one CnaB fold domain as one repeat) are available for collagen-binding Cna of S. aureus (Deivanayagam et al 2000). Despite the availability of these structures, the function of this Cna B-region is still unclear and is hypothesized to be functioning independently from the Cna A-region (Snodgrass et al 1999). Kang et al (2007) reported the presence of a putative isopeptide bond in the structure of Cna B-repeat.…”
Section: Collagen-binding Mscrammsmentioning
confidence: 99%